Peran Produktivitas Dalam Peningkatan Kesejahteraan Petani Padi Di Indonesia - Nur Afiyah Maizunati (Universitas Muhammadiyah Purworejo, 2018)
Achieving food security is one of the global challenges in realizing the Sustainable Development Goals target. The successful growth trend of rice production in Indonesia which is negative can reduce the quality of local producers in providing rice supply to the domestic market and improve the welfare of farmers. Some of the previous studies were obtained from the evidence of income at the farm level with farmer income levels. However, the gap between the results of research with existing conditions in Indonesia. With the wealth indicator being proxied from the exchange rate of farmers, there is still a pattern of a non-linear relationship between economic growth and the exchange rate of farmers in the food crop sub-sector that occurred in Indonesia in several years. Through microdata analysis sourced from the fifth wave of the Indonesian Family Life Survey (IFLS) with Variable Instrumental (IV) regression, this study provides empirical evidence about the production of rice produced on the welfare of rice farmers in Indonesia. At the one percent significance level, a one percent increase in rice production can significantly increase the average income of rice farmers in Indonesia by 0.35 percent (cateris paribus). The welfare of smallholders, in particular, is a component which then complements prioritization in order to support the achievement of food security, one of which is by increasing productivity. Decomposed not only in terms of profit but also in terms of quality. Quality that can be accepted at a significant level, improving education, empowering gender, managing farms that are environmentally friendly, supporting stable prices, independence in fulfilling inputs, capital, marketing, and technological mastery.